Translations in practice: The multiple roles of the researcher in arts-based knowledge exchange. (1st June 2015) - Crawshaw, Julie; Rowe, Frances; Hudson, Martyn
This article is the product of a one-year AHRC experimental pilot project to understand Knowledge Exchange (KE) relationships around the arts in rural Northumberland. There were three strands to the work; Art, Music and Rural Economy with a Research Associate leading on each strand. There were multiple fields in this project; the actual fields of Northumberland and the landscapes in which art and music were practised, the disciplinary fields of the researchers, and the invisible, intangible fields of KE practice. This article reflects on our 'field' work – those interactions in fields of landscape, fields of discipline, and fields of social relations, which provided the context for our interventions. Specifically, this article reflects an experimental and experiential relationship with our 'fields' most potently around the process of entering and leaving those fields and the multiple interaction between ourselves as researchers and our material and cultural landscape. The article concludes with some of the implications of our 'field' practices for future experimental research and the co-production and elaboration of new fields of intervention.